Sustained Release of Cx43 Antisense Oligodeoxynucleotides from Coated Collagen Scaffolds Promotes Wound Healing - Gilmartin, Daniel J. (2016)
Antisense oligodeoxynucleotides targeting the mRNA of the gap junction protein Cx43 promote tissue repair in a variety of different wounds. Delivery of the antisense drug has most often been achieved by a thermoreversible hydrogel, Pluronic F-127, which is very effective in the short term but does not allow for sustained delivery over several days. For chronic wounds that take a long time to heal, repeated dosing with the drug may be desirable but is not always compatible with conventional treatments such as the weekly changing of compression bandages on venous leg ulcers. Here the coating of collagen scaffolds with antisense oligonucleotides is investigated and a way to provide protection of the oligodeoxynucleotide drug is found in conjunction with sustained release over a 7 d period. This approach significantly reduces the normal foreign body reaction to the scaffold, which induces an increase of Cx43 protein and an inhibition of healing. As a result of the antisense integration into the scaffold, inflammation is reduced with the rate of wound healing and contracture is significantly improved. This coated scaffold approach may be very useful for treating venous leg ulcers and also for providing a sustained release of any other types of oligonucleotide drugs that are being developed.